2011
DOI: 10.2214/ajr.10.5180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Abdominal Sonography in the Preoperative Diagnosis of Extrahepatic Biliary Atresia in Infants Younger Than 90 Days

Abstract: Comprehensive sonographic evaluation can help in segregating infants at high risk of EHBA from those at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 19 publications
5
60
1
Order By: Relevance
“…Contractile gallbladder was defined by the change in gallbladder dimensions on ultrasonography 30 min postprandial compared with its basal size after 4 h of fasting. The gallbladder was considered abnormal if no change of its dimensions was observed, if its length was less than 20.5 mm [5], or if it was not visualized [8]. Hepatic histopathological features in the form of portal fibrosis, ductular proliferation, bile plugs, intracellular cholestasis, portal cellular infiltrate, and multinucleated giant hepatocyte were also revised.…”
Section: Data Collectionmentioning
confidence: 99%
“…Contractile gallbladder was defined by the change in gallbladder dimensions on ultrasonography 30 min postprandial compared with its basal size after 4 h of fasting. The gallbladder was considered abnormal if no change of its dimensions was observed, if its length was less than 20.5 mm [5], or if it was not visualized [8]. Hepatic histopathological features in the form of portal fibrosis, ductular proliferation, bile plugs, intracellular cholestasis, portal cellular infiltrate, and multinucleated giant hepatocyte were also revised.…”
Section: Data Collectionmentioning
confidence: 99%
“…US criteria suggesting biliary atresia in the literature are the following: absent or small gallbladder, triangular cord sign and hepatic artery-portal vein diameter ratio [8,20,21]. Although some authors describe the role of hepatic subcaspular flow on color Doppler [22], we did not record this sign in our study.…”
Section: Discussionmentioning
confidence: 70%
“…To date, several sonographic criteria (gallblader size, triangular cord sign, splenomegaly, hepatic artery-portal vein ratio, hepatic subcapsular flow on color Doppler) may point to biliary atresia, but none is diagnostic [8]. Likewise, routine serum measurements are of limited sensitivity and specificity [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the two major causes accounting for 60%-90% of all neonatal cholestasis are neonatal hepatitis and biliary atresia [1]. Discrimination between these two entities is very important, since they require completely different treatment approaches-medical treatment for hepatitis and surgery for biliary atresia.…”
Section: Introductionmentioning
confidence: 99%
“…The concept that a younger age at the diagnosis of and surgery for biliary atresia leads to a better outcome has been generally accepted [1,5-14], while some of the published data have revealed that patient age has no significance or sometimes even a negative effect on the prognosis [15,16]. However, when it comes to type III biliary atresia, the negative effect of older age seems more obvious [9].…”
Section: Introductionmentioning
confidence: 99%